"Testing the water" – prior-online market entry in China. Issue 7 (16th March 2021) - Hardaker, Sina; Zhang, Ling
Abstract : Purpose: The paper aims to investigate the new market entry strategy of the international grocery retailers Aldi Süd and Costco in China; analyzing if and how their prior-online market entry reflects a strategic response to organizational challenges in the Chinese market, which is a pioneer in the use of digital technologies and the provision of digital services. Design/methodology/approach: The article identifies major challenges faced by international grocery retailers in China and discusses these with the help of the conceptual approach of embeddedness. The paper is based on expert interviews with senior executives of the two international retailers and other retail specialists and consultants. Findings: The prior-online market entry by Aldi Süd and Costco represents a strategic response to organizational challenges that have to be faced in an increasingly challenging and highly digitalized Chinese market. Prior-online market entry allows the two retailers to experiment with the unique and heterogeneous Chinese market and build network and territorial embeddedness to facilitate the establishment of the physical store network. Both retailers utilize online stores to build relation and network with suppliers and customers and to understand Chinese consumer preferences. Yet, the localization strategy of Aldi Süd and Costco vary greatly. Originality/value: Grocery retailers' prior-online expansion strategy has not yet been the focus of academic research. In regard to global grocery retailers, such as Aldi Süd and Costco, previous research argued that they were prepared to accept a lower expansion speed in order to expand at minimum risk and cost and mainly in countries which are regarded as having higher cultural proximity. The paper reveals the potential of the prior-online market entry strategy to change the internationalization behavior of grocery retailers. In addition, it contributes to the understanding of the evolution of market entry strategy into advanced digital economies in the coming new decade.